Pemimpin Kelompok sebagai Katalisator : Peran Kunci dalam Efektivitas dan Harmonisasi Dinamika Konseling Kelompok - Ike Nurhidayah; Anasari Anasari; Muhammad Roihan; Fadhilianti Maghfiroh; Ratna Sari Dewi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the role of leaders in group counseling dynamics through a literature review approach. In group guidance practices, leaders serve not only as technical facilitators but also as catalysts who shape healthy and productive interaction structures. The literature review reveals that leadership effectiveness is strongly influenced by interpersonal competence, the guidance strategies employed, and sensitivity to the diverse backgrounds of group members. Techniques such as sociodrama and reflection, along with approaches like Gestalt, Transactional Analysis, and Solution-Focused Brief Counseling (SFBC), have been proven to significantly enhance group dynamics. Additionally, ongoing training is a strategic measure to strengthen leaders’ capacity in managing groups effectively. Therefore, adaptive, empathetic, and reflective leaders play a crucial role in fostering a supportive and transformative group climate.